High precision renormalization of the flavour non-singlet Noether currents in lattice QCD with Wilson quarks - Sint, Stefan (SpringerOpen, 2019)
We determine the non-perturbatively renormalized axial current for O(a) improved lattice QCD with Wilson quarks. Our strategy is based on the chirally rotated Schrödinger functional and can be generalized to other finite (ratios of) renormalization constants which are traditionally obtained by imposing continuum chiral Ward identities as normalization conditions. Compared to the latter we achieve an error reduction by up to one order of magnitude. Our results have already enabled the setting of the scale for the Nf=2+1 CLS ensembles (Bruno et al. in Phys Rev D 95(7):074504. arXiv:1608.08900, 2017) and are thus an essential ingredient for the recent αs determination by the ALPHA collaboration (Phys Rev Lett 119(10):102001. arXiv:1706.03821, 2017). In this paper we shortly review the strategy and present our results for both Nf=2 and Nf=3 lattice QCD, where we match the β-values of the CLS gauge configurations. In addition to the axial current renormalization, we also present precise results for the renormalized local vector current.
PUBLISHED
Keywords: Renormalized local vector current; Wilson quarks; Normalization conditions; Axial renormalization